Intrinsic Motivation and School Climate as Predictors of Teacher Performance in Rural Indonesian Schools - Herli, Herli; Danim, Sudarwan; Kartiwi, Asti Putri; Khairi, Azizatul (Universitas Ahmad Dahlan, 2026)
Background/purpose. Teacher performance is a critical determinant of educational quality, yet it remains challenged by declining motivation and suboptimal work environments, particularly in developing countries. Materials/methods. This study examined the influence of intrinsic motivation and school climate on teacher performance among 72 public junior high school teachers in Empat Lawang District, South Sumatra, Indonesia, using a quantitative cross-sectional survey design. Data were collected through validated questionnaires (intrinsic motivation: α = .960; school climate: α = .866; teacher performance: α = .938) and analyzed using Pearson correlation and multiple regression. Results. Both predictors demonstrated strong positive correlations with teacher performance (intrinsic motivation: r = .907; school climate: r = .826; p < .001). Simple regression revealed that intrinsic motivation accounted for 82.3% of the variance in performance (R² = .823), while school climate accounted for 68.1% of the variance (R² = .681). Multiple regression indicated that both variables jointly explained 84.2% of the variance (R² = .842, F = 183.326, p < .001), with intrinsic motivation emerging as the dominant predictor (β = .707) relative to school climate (β = .243). Conclusion. These findings suggest that improving teacher effectiveness in resource-constrained rural settings requires prioritizing professional autonomy and competency development alongside a supportive organizational climate.